2022
DOI: 10.1542/peds.2022-056726
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin Thromboprophylaxis in Children Hospitalized for COVID-19: A Phase 2 Trial

Abstract: BACKGROUND Evidence regarding the safety and efficacy of anticoagulant thromboprophylaxis among pediatric patients hospitalized for COVID-19 is limited. We sought to evaluate safety, dose-finding, and preliminary efficacy of twice-daily enoxaparin as primary thromboprophylaxis among children hospitalized for symptomatic COVID-19 including primary respiratory infection and multisystem inflammatory syndrome in children (MIS-C). METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 52 publications
0
24
0
2
Order By: Relevance
“…They discussed thromboprophylaxis for those with symptomatic COVID‐19–related illnesses as low‐dose low‐molecular‐weight heparin twice‐daily dosing targeting an anti‐Xa activity level of 0.2 to <0.5 units/ml, with consideration given to additional risk factors for thrombosis 33 . More recently, a Phase 2 trial was published that demonstrated the safety of 0.5 mg/kg/dose twice‐daily dosing with a maximum dose of 60 mg to target an anti‐Xa activity level of 0.2–0.49 IU/ml 34 . These recommendations were published after our participants responded and would likely have increased the number of individuals who would have changed their practice.…”
Section: Discussionmentioning
confidence: 99%
“…They discussed thromboprophylaxis for those with symptomatic COVID‐19–related illnesses as low‐dose low‐molecular‐weight heparin twice‐daily dosing targeting an anti‐Xa activity level of 0.2 to <0.5 units/ml, with consideration given to additional risk factors for thrombosis 33 . More recently, a Phase 2 trial was published that demonstrated the safety of 0.5 mg/kg/dose twice‐daily dosing with a maximum dose of 60 mg to target an anti‐Xa activity level of 0.2–0.49 IU/ml 34 . These recommendations were published after our participants responded and would likely have increased the number of individuals who would have changed their practice.…”
Section: Discussionmentioning
confidence: 99%
“…For children who were clinically unstable or with severe renal impairment the same panel suggested the use of intravenous UFH given by continuous infusion 35 . More recently, the results of an open‐label, multicenter phase 2 trial among 40 children <18 years of age hospitalized for primary COVID‐19 with or without PMIS found twice‐daily enoxaparin thromboprophylaxis (0.5 mg/kg/dose; max of 60 mg/dose) to be safe in achieving target anti‐Xa levels without observed clinically relevant bleeding or related serious adverse events 36 . As such, twice daily weight‐based LMWH at half the treatment dose should be considered for primary thromboprophylaxis in children hospitalized for COVID‐19 with or without PMIS.…”
Section: Hospitalization Periodmentioning
confidence: 99%
“…For patients older than 18 years of age cared for in pediatric centers, it is reasonable to follow adult guidelines, which are based on high-quality, randomized controlled trial data [27 && ,28 && ]. The COVID-19 Anticoagulation in Children -Thromboprophylaxis (COVAC-TP) trial is the only pediatric study evaluating the safety of thromboprophylaxis in children [50]. This study evaluated the safety of low dose LMWH targeting an anti-Xa level of 0.2-0.49 IU/mL in 38 children.…”
Section: Thrombotic Events In Children With Coronavirus Disease 2019 ...mentioning
confidence: 99%
“…The COVID-19 Anticoagulation in Children – Thromboprophylaxis (COVAC-TP) trial is the only pediatric study evaluating the safety of thromboprophylaxis in children [ 50 ]. This study evaluated the safety of low dose LMWH targeting an anti-Xa level of 0.2–0.49 IU/mL in 38 children.…”
Section: Thromboprophylaxis In Children With Coronavirus Disease 2019...mentioning
confidence: 99%
See 1 more Smart Citation